Child Friendly Education and Its Implication in Establishing Humanist Teacher’s Profile: Considering ‘Abdullāh Nāshih ‘Ulwān’s Thought - Naili Rohmah Iftitah; Siswanto Siswanto (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The occurrence of violence in education is caused by the poor education system. Considering the thought of the Islamic educational figure is a wise act because his thought is inspired by the values of Islamic teachings as the religion of raḥmah li al-'ālamīn. This study employed a qualitative approach. This study found several important findings. First, the concept of child-friendly education includes three terms including affection (al-raḥmah), graceful (al-rifq wa al-layn), and justice (al-‘adālah). Second, child-friendly education methods consist of education with exemplary, education with customs, education with advice, education with attention, and education with punishment. Furthermore, the implication to establish humanist teachers is to develop teachers’ four competency domains including humanistic values, treating students affectively, graceful, and justice, as well as protecting them from all acts of violence. By doing this, the teachers will become more religious, professional, and inspirative.